2022
DOI: 10.1371/journal.pone.0275500
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between hospital staffing levels and inpatient-COVID-19 mortality rates?

Abstract: Objective This study aims to investigate the relationship between RNs and hospital-based medical specialties staffing levels with inpatient COVID-19 mortality rates. Methods We relied on data from AHA Annual Survey Database, Area Health Resource File, and UnitedHealth Group Clinical Discovery Database. In phase 1 of the analysis, we estimated the risk-standardized event rates (RSERs) based on 95,915 patients in the UnitedHealth Group Database 1,398 hospitals. We then used beta regression to analyze the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…For example, hospitals equipped to perform open heart surgeries were used as proxy for more advanced equipment and technological capacity than those who do not perform open heart surgery, but it is unclear whether this denotes a substantive difference in organizational capacity or resources compared to a hospital that does not perform open heart surgeries. Data suggests that community level factors such as urbanicity, county socioeconomic status, and housing type may shape the patient population served by the organization, which impacts both care delivery and outcomes,(10) so these factors need to be considered when examining the impacts of staffing and workforce issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, hospitals equipped to perform open heart surgeries were used as proxy for more advanced equipment and technological capacity than those who do not perform open heart surgery, but it is unclear whether this denotes a substantive difference in organizational capacity or resources compared to a hospital that does not perform open heart surgeries. Data suggests that community level factors such as urbanicity, county socioeconomic status, and housing type may shape the patient population served by the organization, which impacts both care delivery and outcomes,(10) so these factors need to be considered when examining the impacts of staffing and workforce issues.…”
Section: Discussionmentioning
confidence: 99%
“…Patient outcomes also differ due to characteristics such as comorbidities, mental health problems, and social determinants of health (SDOH), a set of social and environmental factors underlying health inequities. (10) Increases in inpatient assessment of SDOH have improved the care teams’ ability to identify patients with higher social and support needs; those needs require interprofessional services and support alongside nursing care to improve equity and optimize patient outcomes. (11) With ongoing shortages of healthcare workers across multiple professions and documented burnout among RNs, it is critical to understand how care team composition in acute care settings affects outcomes for both patients and workers.…”
Section: Introductionmentioning
confidence: 99%
“…In the present review, we found that interventions that focus on staff resources may also help reduce the use of MR. This is not surprising as increased staffing has repeatedly proven to optimise healthcare services, including during the recent coronavirus pandemic (Al‐Amin et al., 2022). However, other ways may also be used to improve interventions between patients and staff to reduce MR beyond those identified in this review.…”
Section: Discussionmentioning
confidence: 99%